Managing wet fen meadows for nature conservation leads to a moderate warming effect - Reinhard Wolf; Vytas Huth; Florian Jansen (Mires and Peat)
Wet fen meadows under traditional land use are nowadays mainly preserved through nature conservation measures. Recent discussions suggest that this land use may also be regarded as a form of paludiculture - that is, use of wet peatland with preservation of the peat body. However, the climate effect of this land use type is largely unknown. This study presents full two-year greenhouse gas (GHG) balances for two previously unexplored, long-term rewetted fens under a nature conservation management regime. Closed-chamber GHG fluxes were measured biweekly at two north-east German sites with acute sedge (Carex acuta) and at one site with creeping bentgrass (Agrostis stolonifera). Including harvest and dissolved carbon export, the CO2-eq emissions of the three sites were between 10.4 and 16.3 t ha-1 yr-1, with mean annual water levels between -10 and -19 cm relative to ground level. Emissions consisted mainly of CO2 uptake and release and were influenced by the timing and frequency of harvests as well as by periods of surface flooding during the growing season. CH4 emissions also contributed to the net GHG balances at two of the sites due to inundation in late summer 2014. N2O emissions were of minor importance at all three sites. This study shows that, with proper water management, the climate effect of fen meadows under management for nature conservation can be similar to that of other fen paludicultures, with a CO2-eq GHG mitigation potential of 15–20 t ha- 1 yr-1 compared to drainage-based grassland use of fens. Therefore, for GHG reporting purposes, it may be justifiable to treat existing wet fen meadows under nature conservation management as paludicultures.